2016
DOI: 10.1111/nyas.13098
|View full text |Cite
|
Sign up to set email alerts
|

The stimulated social brain: effects of transcranial direct current stimulation on social cognition

Abstract: Transcranial direct current stimulation (tDCS) is an increasingly popular noninvasive neuromodulatory tool in the fields of cognitive and clinical neuroscience and psychiatry. It is an inexpensive, painless, and safe brain-stimulation technique that has proven to be effective in modulating cognitive and sensory-perceptual functioning in healthy individuals and clinical populations. Importantly, recent findings have shown that tDCS may also be an effective and promising tool for probing the neural mechanisms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 184 publications
4
79
0
Order By: Relevance
“…Despite consistent behavioural evidence for the efficacy of tDCS to affect social cognitive processes (Sellaro et al, 2016), little is known about how tDCS affects brain function. However, recent evidence suggests that HD-tDCS to the rTPJ increases low-frequency oscillatory activity that may exert inhibitory effects at the network-level and enable switching between endogenous and exogenous processing streams (Donaldson et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Despite consistent behavioural evidence for the efficacy of tDCS to affect social cognitive processes (Sellaro et al, 2016), little is known about how tDCS affects brain function. However, recent evidence suggests that HD-tDCS to the rTPJ increases low-frequency oscillatory activity that may exert inhibitory effects at the network-level and enable switching between endogenous and exogenous processing streams (Donaldson et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an important discussion surrounding tDCS research is related to how reproducibility of reported effects should be evaluated49. A recent review50 on the effects of tDCS on social cognition pointed out that some studies produced results inconsistent to each other, likely due to methodological differences (e.g., intensity and duration of the stimulation, online vs. offline stimulation, electrode size, scalp placement, study design, experimental task). Therefore, more research, based on larger samples, different tasks, and including population of patients with ToM deficit, is needed to elucidate the reasons for these discrepancies and to verify whether the observed tDCS-induced changes in social cognition are maintained across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Results are very preliminary, however, and no studies have examined the impacts of TPJ modulation in terms of social‐cognitive performance relevant to autism. Nor have prior studies examined neurophysiological correlates of behavioural outcomes, which is important in terms of understanding the spatiotemporal effects of stimulation protocols, identifying potential candidate neurological mechanisms of modulatory effects and increasing the likelihood/possibility of translational clinical applications (Shafi et al ., ; Sellaro et al ., ). One way to begin exploring in this regard is by utilising the notion that autism‐relevant traits extend into the general population in a continuum (Constantino & Todd, ; Jung et al ., ; Ruzich et al ., ).…”
Section: Introductionmentioning
confidence: 97%